Kesantunan Bersosial Media Dan Gawai Pada Siswa SMP - Widiyarto, Sigit; Ronald Haries Hamonangan; Nia Damayanti; Sutina, Sutina; Toto Widiarto (Jurnal Pengabdian UntukMu NegeRI, 2022)
The use of social media and gadgets in junior high school students was still a dilemma for parents. On the one hand it could help learning, but on the other hand it was still a problem, if you can't use it properly. Various problems would arise if students do not have sufficient knowledge in using social media and gadgets. The activity was carried out from March to May 2022 at the Alihsan Middle School in Bekasi City. The number of students who participated were 27 students of class VII. Guidance techniques were carried out individually and in groups. Online presentation techniques, discussions between the abdimas team and participants, and question and answer sessions. The results of the activity showed that students were able to understand the use of gadgets and effective ways of social media. The average value of students in both theory and practice is 75. Keywords: social media; device; junior high school students